PROFITABILITY MEDIATES THE INFLUENCE OF LEVERAGE, LIQUIDITY AND COMPANY SIZE ON TAX AGGRESSIVENESS - Silvi Fadillah; Lady Andriani; Mohamad Zulman Hakim; Dewi Rachmania; Samino Hendrianto (ZILLZELL MEDIA PRIMA, 2025)
This study examines the determinants of tax aggressiveness in Indonesia's Basic Materials sector, focusing on the effects of leverage, liquidity, company size, and profitability, with profitability serving as a potential mediating variable. The research employs quantitative panel data regression analysis using secondary data from 13 companies listed on the Indonesia Stock Exchange during the 2019-2023 period, resulting in 65 firm-year observations. Data were analyzed using EViews 12 with Common Effect Model and Random Effect Model estimation based on hypothesis testing results. The results indicate that profitability significantly negatively affects tax aggressiveness, while leverage, liquidity, and company size show no significant direct effects. Leverage demonstrates a significant negative impact on profitability, but liquidity and company size do not significantly influence profitability. The Sobel test confirms that profitability does not mediate the relationships between financial characteristics and tax behavior. The findings suggest that regulators should focus monitoring efforts on profitability metrics rather than conventional indicators like company size or leverage when assessing tax compliance risks. Companies should recognize that transparent tax strategies can complement strong financial performance rather than detract from it. This research provides novel insights into the contradictory role of conventional determinants of tax aggressiveness in emerging markets and demonstrates the complex relationship between profitability and tax behavior in Indonesia's Basic Materials sector.